ANALYZING PRESTIGE PRICING STRATEGY OF PRIVATE DORM IN MANADO - Sitorus, Freddy S.H; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2019)
Abstract: In this era, the number of business in Indonesia is vast. In Manado itself people tend to choose an office job rather than making their own business. One of the business that people can open with low requirement and high profit that is private dorm business. The number of private dorm in Manado is quite high, thats why people who think to make the business need to find a strategy that not many people used but have a great impact on their business, that is prestige pricing strategy. This study aims to analyzing how the prestige pricing strategy works in private dorm business in Manado. This research uses Qualitative Method with In-depth Interview, in order to know the success of prestige pricing strategy in private dorm business in Manado. The result of this research show advantages of prestige pricing strategy in private dorm business is toward the features and its luxury. Thes service and price policy is one of the strongest point too. From the result, the researcher think that using the prestige pricing strategy for private dorm business is very promising but can be a little bit expensive so the owner need to think carefully and consider what they need to purchase or not to purchase for their private dorm business. Keyword : service, private dorm, prestige pricing strategy